Response of the fungus Pseudocercospora griseola f. mesoamericana to Tricyclazole - Bárcena, Alejandra (2015)
Pseudocercospora griseola, an anamorph of Mycosphaerella, causes Angular Leaf Spot (ALS). The mycelia and conidia from P. griseola are coloured due to the synthesis of 1,8 dihydroxynaphthalene (DHN)-melanin. The aim of this work was to identify in P. griseola f. mesoamericana isolate T4, a highly pigmented fungus, intermediary compounds as a result of the inhibition of melanin synthesis by tricyclazole, and to analyze at the structural level the localization of these dark pigments. The main metabolites were analyzed using ultraviolet matrix-assisted laser desorption-ionization mass spectrometry (UV–MALDI MS). Tricyclazole affected P. griseola f. mesoamericana in several different ways. The most evident effect was the reduction of melanin synthesis, and therefore diffusible shunt products were found and identified. Flaviolin was the main intermediate metabolite found in cultures supplemented with tricyclazole. This inhibitor, which affected pigmentation and the cell wall structure of mycelium, revealed macroscopically by the reduction in growth, decreased the stratification and deposition of melanin in the hyphal wall. These results suggest a possible role of tricyclazole to control ALS.